Bambusicolous Arthrinium Species in Guangdong Province, China - Senanayake, Indunil C.; Bhat, Jayarama D.; Cheewangkoon, Ratchadawan; Xie, Ning (Frontiers in Microbiology, 2020)
A survey of bambusicolous fungi in Bijiashan Mountain Park, Shenzhen, Guangdong Province, China, revealed several Arthrinium-like taxa from dead sheaths, twigs, and clumps of Bambusa species. Phylogenetic relationships were investigated based on morphology and combined analyses of the internal transcribed spacer region (ITS), large subunit nuclear ribosomal DNA (LSU), beta tubulin (β-tubulin), and translation elongation factor 1-alpha (tef 1-α) gene sequences. Based on morphological characteristics and phylogenetic data, Arthrinium acutiapicum sp. nov. and Arthrinium pseudorasikravindrae sp. nov. are introduced herein with descriptions and illustrations. Additionally, two new locality records of Arthrinium bambusae and Arthrinium guizhouense are described and illustrated.